2006
DOI: 10.1128/aem.01187-06
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mutations in the Substrate-Binding Domain of Poly[( R )-3-Hydroxybutyrate] (PHB) Depolymerase from Ralstonia pickettii T1 on PHB Degradation

Abstract: Poly[(R)-3-hydroxybutyrate] (PHB) depolymerase fromRalstonia pickettii T1 (PhaZ RpiT1 ) adsorbs to denatured PHB (dPHB) via its substrate-binding domain (SBD) to enhance dPHB degradation. To evaluate the amino acid residues participating in dPHB adsorption, PhaZ RpiT1 was subjected to a high-throughput screening system consisting of PCR-mediated random mutagenesis targeted to the SBD gene and a plate assay to estimate the effects of mutations in the SBD on dPHB degradation by PhaZ RpiT1 . Genetic analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 37 publications
1
33
0
3
Order By: Relevance
“…In contrast to the high sequence homology in the N-terminal regions among PhaR homologs, sequence similarity is partly distributed in the predicted P(3HB)-binding motif region shared by PhaR family members. The next project has been initiated to address the amino acid residues of PhaR responsible for binding to P(3HB) by two approaches, X-ray crystallographic analysis and further random mutagenesis analysis, as also employed for a member of the granule-associated proteins, P(3HB) depolymerase (10,11).…”
Section: Vol 189 2007mentioning
confidence: 99%
“…In contrast to the high sequence homology in the N-terminal regions among PhaR homologs, sequence similarity is partly distributed in the predicted P(3HB)-binding motif region shared by PhaR family members. The next project has been initiated to address the amino acid residues of PhaR responsible for binding to P(3HB) by two approaches, X-ray crystallographic analysis and further random mutagenesis analysis, as also employed for a member of the granule-associated proteins, P(3HB) depolymerase (10,11).…”
Section: Vol 189 2007mentioning
confidence: 99%
“…The difference in the crystal structure influenced the enzymatic degradation. Absorption research on R. pickettii T1 depolymerase mutant on PHA revealed that the absorption depended not only on hydrogen bonds between hydroxyl groups of serine in the enzyme and carbonyl groups in the PHB polymer, but also on hydrophobic interaction between hydrophobic residues in the enzyme and methyl groups in the PHB polymer (Hiraishi et al 2006;Abe et al 2005). The number of PHB depolymerase enzyme molecules adsorbed on each single crystal increased in the following order: poly(3HB-co-8 mol% 3HH) < PHB » poly(3HB-co-6 mol% 3HV), where 3HH is (R)-3-hydroxyhexanoate.…”
Section: Short-chain-length Phasmentioning
confidence: 99%
“…The substrate-binding domain is responsible for the enzyme adsorption to the polymer surface as well as the disruption of the polymer surface structure, resulting in the easy access of the catalytic domain to the polymer chains. [9][10][11][12][13][14][15][16] It is possible that such domain structure of PHB depolymerase is responsible for the effective enzymatic degradation of PHB at the solid/liquid interface. Besides its excellent ability to depolymerize the biosynthesized PHB, because PHB depolymerase is derived from renewable resources, this enzyme shows great promise as a low-cost, human-friendly, and environmentally compatible catalyst for PHB monomer production by serving as an alternative to chemical catalysts.…”
Section: Introductionmentioning
confidence: 99%